Determinant Harga Saham Perusahaan Sektor Pertambangan di Bursa Efek Indonesia - Achmad Nizar Hidayat; Yuyun Isbanah (BISMA (Bisnis dan Manajemen), 2018)
The purpose of this research is to analyze the influence of debt ratio, size, earnings per share, dividend policy, and money supply to stock price in mining Sector Company listed in Indonesia stock exchange period 2011-2015. This research uses the type of causality research and the data used is secondary data. Sampling technique by purposive sampling and obtained by eight companies as research object. The analysis method used is multiple linear regression analysis. The results show the debt ratio, size, earnings per share, dividend payout ratio, and dividend yield effect on stock prices of mining companies. While the money supply does not affect to stock price of mining companies. The recommendation of this research is that company need to consider debt ratio, size, earnings per share, dividend payout ratio and dividend yield in making company policy, because can affect stock price movement of company and become an alternative investment decision-making for investors.